(untitled) (CIPEEX, 2026)
Introduction: The internet has made access to information easier, but it has also facilitated the spread of false contente fake News which, in the health field, can compromise treatments, reduce adherence to preventive measures, and impact scientific credibility. Objective: To describe the experience of an extension activity, linked to the Scientific Methodology course, from the perspective of a Nursing undergraduate student, addressing the impacts of fake news on the population. Methodology: A descriptive-reflective experience report developed during the first semester of the Nursing program (2025.1). The activity included a lecture, group discussions, preparation of critical summaries, production of an educational video, and creation of pamphlets distributed to the community. Results and Discussion: The action resulted in the creation of a video and a pamphlet with a QR Code addressing the risks of fake news related to encapsulated products, encouraging research, critical analysis, scientific communication, teamwork, and creativity. The materials were shared on social media and the institution’s official page, receiving positive feedback from both the community and the institution, demonstrating effective integration between theory and practice. Conclusion: The experience strengthened academic and social competencies, reinforced the importance of verifying health-related information, and highlighted the role of Nursing in promoting scientific citizenship and social responsibility. Keywords: Fake news; Public health; Nursing education; University outreach.